The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.2134/agronj1991.00021962008300010039x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Salinity and Temperature on the Germination of Crambe

Abstract: Crambe (Crambe abyssinica Hochst. ex R.E. Fries) is a potential oilseed crop for semiarid and arid environments where saline irrigation waters and soils are common. Crambe tolerance to salinity during germination is unknown. A laboratory experiment was designed to determine salinity tolerance of crambe during germination and salinity ✕ temperature interactions that may influence germination and stand establishment. Treatment solutions were prepared using NaCl and CaCl2 in a 2:1 molar ratio. Salinity (electrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
0
7

Year Published

1992
1992
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 8 publications
1
28
0
7
Order By: Relevance
“…Stone et al (1979) announced that medicago in the beginning stages of growth is more sensitive to salinity and there is a reciprocal influence between levels of saltiness to percentage of seed germination. Thus, the results of Flower (1991) showed that the germination percentage reduction of crambe abyssinica reach to a maximum temperature of 30°C by increasing salinity and time. Whereas in temperatures of 15 and 25°C, salinity has no important influence on decreasing of germination percentage.…”
Section: Introductionmentioning
confidence: 91%
“…Stone et al (1979) announced that medicago in the beginning stages of growth is more sensitive to salinity and there is a reciprocal influence between levels of saltiness to percentage of seed germination. Thus, the results of Flower (1991) showed that the germination percentage reduction of crambe abyssinica reach to a maximum temperature of 30°C by increasing salinity and time. Whereas in temperatures of 15 and 25°C, salinity has no important influence on decreasing of germination percentage.…”
Section: Introductionmentioning
confidence: 91%
“…surge com potencial para a produção de óleo destinado à fabricação de biodiesel em estação fria, energia limpa e renovável, em substituição aos combustíveis fósseis, auxiliando na contenção da emissão de gases de efeito estufa. É uma cultura oleaginosa capaz de tolerar temperaturas de até -6,0 ºC por algumas horas sem danos significantes (Fowler, 1991). Durante o período vegetativo necessita temperaturas entre 15 ºC e 25 ºC (Falasca et al, 2010) Dentre as principais características da cultura está sua precocidade, com grãos maduros aos 90/100 dias, boa produtividade, podendo atingir 2.500 kg ha -1 , adaptação a variadas condições pedoclimáticas (Lazzeri et al, 1995;Lessman e Meier, 1972;White e Higgins, 1966) e maturação uniforme, facilitando a colheita mecanizada (Falasca et al, 2010).…”
Section: Introductionunclassified
“…Saline soil and saline irrigation water present potential hazards to canola production (Fowler, 1991). Therefore, it ranks first among field oil crops that withstand stressed conditions and by using tissue cultures we could increase salt tolerance of canola by induction of somaclonal variation (Larkin & Scowcroft, 1981).…”
Section: Introductionmentioning
confidence: 99%